Comprehensive Analysis of Non-coding RNA Profiles of Exosome-Like Vesicles From the Protoscoleces and Hydatid Cyst Fluid of Echinococcus granulosus - Zhang, Xiaofan; Gong, Wenci; Cao, Shengkui; Yin, Jianhai; Zhang, Jing; Cao, Jianping; Shen, Yujuan (Frontiers in Cellular and Infection Microbiology, 2020)
Cystic echinococcosis is a worldwide chronic zoonotic disease that threatens human health and animal husbandry. Exosome-like vesicles (ELVs) have emerged recently as mediators in the parasite–parasite intercommunication and parasite–host interactions. Exosome-like vesicles from parasites can transfer non-coding RNAs (ncRNAs) into host cells to regulate their gene expression; however, the ncRNAs profiles of the ELVs from Echinococcus granulosus remain unknown. Here, we isolated protoscolece (PSC)–ELVs and hydatid fluid (HF)–ELVs from the culture medium for E. granulosus PSCs in vitro and the HF of fertile sheep cysts, respectively. The microRNA (miRNA), long non-coding RNA (lncRNA), and circular RNA (circRNA) profiles of the two types of ELVs were analyzed using high-throughput sequencing, and their functions were predicted using Gene Ontology enrichment and Kyoto Encyclopedia of Genes and Genomes pathway analysis. In PSC–ELVs and HF–ELVs, 118 and 58 miRNAs were identified, respectively, among which 53 miRNAs were present in both ELVs, whereas 65 and 5 miRNAs were unique to PSC–ELVs and HF–ELVs, respectively; 2,361 and 1,254 lncRNAs were identified in PSC–ELVs and HF–ELVs, respectively, among which 1,004 lncRNAs were present in both ELVs, whereas 1,357 and 250 lncRNAs were unique to PSC–ELVs and HF–ELVs, respectively. Intriguingly, the spilled PSCs from cysts excrete ELVs with higher numbers of and higher expression levels of miRNAs and circRNAs than HF–ELVs. The miRNA sequencing data were validated by quantitative reverse transcription–polymerase chain reaction. Furthermore, the target lncRNAs and mRNAs regulated by the 20 most abundant miRNAs were screened, and a ceRNA regulatory network containing 5 miRNAs, 41 lncRNAs, and 23 mRNAs was constructed, which provided new ideas and the molecular basis for further clarification of the function and mechanism of E. granulosus ELVs ncRNAs in the parasite–host interactions. Egr-miR-125-5p and egr-miR-10a-5p, sharing identical seed sites with host miRNAs, were predicted to mediate inflammatory response, collagen catabolic process, and mitogen-activated protein kinase cascade during parasite infections. In conclusion, for the first time, we identified the ncRNAs profiles in PSC–ELVs and HF–ELVs that might be involved in host immunity and pathogenesis, and enriched the ncRNAs data of E. granulosus. These results provided valuable resources for further analysis of the regulatory potential of ncRNAs, especially miRNAs, in both types of ELVs at the parasite–host interface.